1990
DOI: 10.1007/bf00914091
|View full text |Cite
|
Sign up to set email alerts
|

Production of arachidonic and linoleic acid metabolites by guinea pig tracheal epithelial cells

Abstract: Pulmonary epithelial cells may be responsible for regulating airway smooth muscle function, in part by release of fatty acid-derived mediators. Incubation of isolated guinea pig tracheal epithelial cells with radiolabeled arachidonic acid (AA) leads to the production of 5- and 15-hydroxyeicosatetraenoic acid (5- and 15-HETE) and smaller amounts of leukotriene (LT) B4 and C4 and 12-hydroxyheptadecatrienoic acid (HHT). Epithelial cells also are able to release linoleic acid (LA) metabolites. Incubation with radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…ct-Adrenoreceptor agonists were shown to relax rat tracheal segments in an epithelium-dependent manner [1]. It has been suggested that ct-adrenoreceptors are located on the membrane of epitheliocytes and stimulate the production of relaxing factor through the cytosolic calcium mobilization [9,10]. It was shown that smooth muscle guanylate cyclase is involved in the regulation of epithelium-dependent relaxation revealed and is the target of NO and NO-producing compounds [2,8].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ct-Adrenoreceptor agonists were shown to relax rat tracheal segments in an epithelium-dependent manner [1]. It has been suggested that ct-adrenoreceptors are located on the membrane of epitheliocytes and stimulate the production of relaxing factor through the cytosolic calcium mobilization [9,10]. It was shown that smooth muscle guanylate cyclase is involved in the regulation of epithelium-dependent relaxation revealed and is the target of NO and NO-producing compounds [2,8].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, many researchers have noted a high concentration of eicosanoids in the airway wall epithelium and attributed epithelial relaxing effects to AA metabolites (prostaglandin E 2, prostacyclins) [9,11 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that fish oil, which contains n-3 fatty acids, possesses analgesic property and is used in various inflammatory disorders to alleviate pain [17,19,23,52]. Further, since SO is chiefly composed of linoleic acid, it may be possible that it is metabolized to 9- and 13-hydroxy-octadecadienoic acids (HODEs) [53,54] apart from AA and reduce the pain threshold in mice fed SO supplemented diet. Since formation of HODEs is inhibited by COX and LOX inhibitors [53,55], supplementing n-3 fatty acids may preferentially utilize these enzymes for the production of less potent PGE3 and LTB5.…”
Section: Discussionmentioning
confidence: 99%
“…This labile intermediate is further reduced to its 13-hydroxy derivative, 13-hydroxylinoleic acid (13-HODE). 13-HODE is present in and can be produced by several cell types including endothelial cells (Buchanan et al, 1985), neutrophils (Sobermann et al, 1985), epithelial cells (Oosthuizen et al, 1990) and macrophages (Engels et al, 1986). However, the biological activity of 13-HODE has been mainly investigated in vitro.…”
Section: Introductionmentioning
confidence: 99%